Pengaruh layanan account representative terhadap kepatuhan wajib pajak melalui mediasi kepuasan wajib pajak - Firmando Saragih; Ferry Laurensius (Forum Kerjasama Pendidikan Tinggi, 2021)
The purpose of the study was to determine the direct effect of the account representative service variable on taxpayer compliance through mediation of taxpayer satisfaction at KPP Pratama Medan Polonia. The object of the research is corporate taxpayers who are registered at KPP Pratama Medan Polonia. Data was collected using a questionnaire sent to 99 corporate taxpayer respondents to determine the taxpayer's perception of each research variable. Testing the validity and reliability of the data was carried out to ensure that the respondents' answers reflected the research variables. The analytical tool used is path analysis using SPSS. The results showed that the account representative service had a positive effect on corporate taxpayer satisfaction, and corporate taxpayer satisfaction had no effect on corporate taxpayer compliance. In this study, it is also known that the account representative service variable has a significant effect on corporate taxpayer compliance through mediation of taxpayer satisfaction.